Exploring the Intensity of Corrective Feedback in Online English Instruction: A Study of Synchronous and Asynchronous Modes - Muhayyang, Maemuna; Novia, Lely (Har Press Indonesia, 2025)
This research examines the degree of intensity in the delivery of corrective feedback (CF) by EFL lecturers within online English language instruction, with particular attention to synchronous and asynchronous communication modes. Adopting a descriptive qualitative framework, the study gathered data through classroom observations and in-depth interviews with eight lecturers teaching various English courses at Universitas Negeri Makassar. The analysis centered on three principal dimensions of feedback intensity: attention, duration, and frequency. The results indicated that CF provided via synchronous platforms—such as video conferencing or real-time chat—was generally more immediate, intensive, and frequent. This mode enabled lecturers to address student errors dynamically and offer direct feedback that fostered metacognitive engagement and timely revisions. Conversely, CF delivered asynchronously through tools such as email, discussion forums, and learning management systems was found to be less intensive, broader in scope, and delayed, often influenced by limited student engagement and the self-directed nature of asynchronous interaction. Despite these differences, asynchronous feedback facilitated more deliberate and structured responses. The study underscores that CF intensity is influenced by technological capabilities, the nature of the course content, and the frequency of lecturer-student interaction. It concludes that a strategic integration of both synchronous and asynchronous feedback modalities can significantly improve the effectiveness of online English language instruction.